A study on Ilonggo vocal music - Bordon, Ariel Ynion (1995)
The primary aim of this paper is to present some folksongs coming from the province of Iloilo. This songs reveal the Ilonggos as a people : simple, humble, hospitable, hardworking, and musical. Moreover, it is said that the Ilonggos are melodious when they speak. They seem to sing instead of speak. Such is due to their Hiligaynon language - mellow, flexible, friendly, and musical in itself.
Computer print-out (photocopy).
Thesis (B.M.)--University of the Philippines, Diliman.
Keywords: Folk-songs, Philippine--Iloilo.; Music--Philippines--Iloilo.; Iloilo--Social life and customs; Hiligaynon (Philippine people)--Philippines--Iloilo--Music.